Annual World Bank Conference on Development Economics 2001/2002 - Pleskovic, Boris (Washington, DC: World Bank, 2013)
The Annual World Bank Conference on Development Economics is a forum for discussion, and debate of important policy issues facing developing countries. This report for 2001-2002 focuses on two main themes, based on papers presented, and discussions that followed: 1) globalization and inequality, drawing on historical trends, through the human capital nexus, and the role of foreign trade and investment, to the geographic and international inequalities of globalization, and how the impact of technological change affected the developing world; and, 2) health and development, focused on the role of nongovernmental organizations in the provision of health care, with a special look at the patent policy proposal for global diseases. Health, income, and economic development are emphasized, so as to highlight the world inequality, and the growing concerns on the rising longevity.